Allusion as one of the key components of the headlines of publicistic mediatexts - Yulia Kalanzhiy (Ибероамериканские тетради)
The periodical press reflects modern reality, and the newspaper text becomes that integral element of modern society, which influences on social behavior, forms mass consciousness creates some myths and deconstructs the others. With the development of the Internet and the means of communication, the publicist text began to develop a new “environment”, gradually assimilating in the virtual space, creating a new phenomenon, a media text, which is of special interest for researchers.The headline in the publicist media text serves as an attraction that makes the recipient pay attention to the proposed publication, go over the hyperlink and create a motivation to get acquainted with the main material of the article. In this vein, special attention is paid to the use of artistic means-irony, language games, metaphors, allusions, etc., since in the context of publicist discourse they become the main style-building components and attractive triggers. In our study, we consider allusion as one of the key components of the headline of publicist media text, as it reflects the culture layer that is common to the addressee and the recipient, thereby marking a certain cultural paradigm that dominates the given society.Thus, the aim of our research is to analyze and systematize the basic principles of functioning of allusion in the headlines of publicist texts from the positions of media linguistics.